Operational Strategies for Battery Energy Storage Systems for Corrective Congestion Management - Richter, Julian; Porst, Johannis (PESS 2021, 2021)
In order to decrease the costs of congestion management and due to the lack of public acceptance for new power lines, new technologies for system operation need to be found. One of those new technologies are large-scale battery energy storage systems (BESS). Hereby, the BESS is connected to the transmission grid where it contributes to congestion management. This paper analyzes operational strategies proposed by German TSOs for corrective congestion management via lookup tables and a novel voltage angle control is introduced as a first step towards automatic system operation. These strategies are tested on a line outage in IEEE’s 39-bus-system. While the usage of a pair of BESS is not very effective regarding congestion management due to limited impact, the positive impact on congestion management could be observed during the usage of four BESS. The voltage angle control showed potential to be a suitable option regarding automatic system operation.<br